Towards a global agenda on migration and development ? : evidence from Senegal - (:unkn) unknown (My University, 2013)
The migration-development nexus has been of increasing importance in international relations between African and European countries since 2000. Linking migration to development has spurred political interest in the development potential of migrants as a substitute for official development assistance. This paper analyses the convergence in discourse and practices on migration and development in the context of migration policies formulated to manage migration between Africa and Europe. The discourse on migration and development is mobilised by different actors to justify their actions; it stems from different migration management concepts and frameworks advocated by the European Union, particularly in its Global Approach to Migration. The migration and development discourse is sustained by increased funding from the European Union and some member states to instil a particular view of the nexus between migration and development. The case of Senegal in this paper illustrates the application of the dominant discourse. The first section provides an analysis of the discourse mobilised by different actors at the European and African levels to justify the promotion of the migration-development nexus. The second section scrutinises the practices and roles of the actors involved in the design and implementation of recent programmes in Senegal.
Keywords: African Research